Consistent, small effects of treefall disturbances on the composition and diversity of four Amazonian forests. (17th January 2016) - Baker, Timothy R.; Vela Díaz, Dilys M.; Chama Moscoso, Victor; Navarro, Gilberto; Monteagudo, Abel; Pinto, Ruy; Cangani, Katia; Fyllas, Nikolaos M.; Lopez Gonzalez, Gabriela; Laurance, William F.; Lewis, Simon L.; Lloyd, Jonathan; et al.
Summary: Understanding the resilience of moist tropical forests to treefall disturbance events is important for understanding the mechanisms that underlie species coexistence and for predicting the future composition of these ecosystems. Here, we test whether variation in the functional composition of Amazonian forests determines their resilience to disturbance. We studied the legacy of natural treefall disturbance events in four forests across Amazonia that differ substantially in functional composition. We compared the composition and diversity of all free‐standing woody stems 2–10 cm diameter in previously disturbed and undisturbed 20 × 20 m subplots within 55, one‐hectare, long‐term forest inventory plots. Overall, stem number increased following disturbance, and species and functional composition shifted to favour light‐wooded, small‐seeded taxa. Alpha‐diversity increased, but beta‐diversity was unaffected by disturbance, in all four forests. Changes in response to disturbance in both functional composition and alpha‐diversity were, however, small (2 – 4% depending on the parameter) and similar among forests. Synthesis . This study demonstrates that variation in the functional composition of Amazonian forests does not lead to large differences in the response of these forests to treefall disturbances, and overall, these events have a minor role in maintaining the diversity of these ecosystems. Abstract : Understanding how the diversity of tropical forests responds to treefall disturbance events is important for understanding mechanisms of species coexistence and for predicting the future composition of these ecosystems. Previous studies have focussed on single sites and have contradictory results. By studying four sites in Amazonia, we demonstrate that these events have a consistent, but minor, role in maintaining the diversity of these ecosystems.